Retinoic acid ortho-hydroxy aniline amide promotes neurotrophin mediated cell growth and proliferation in nerve cells - Wang, Zhi-Gang; Wang, Jin-Peng; Wang, Fang; Wang, Yi-Hua; Cao, Pei-Cheng (Bangladesh Journal of Pharmacology, 2015)
In the present study, effect of retinoic acid ortho-hydroxy aniline amide (RAA), an analog of retinoic acid (RA) was investigated on neurotrophin mediated cell growth and proliferation in hippocampus-derived stem cell clones. The results revealed that retinoic acid ortho-hydroxy aniline amide enhanced neuronal differentiation, increased NeuroD expression and p21 compared to proliferating cells stimulated by FGF-2. Retinoic acid ortho-hydroxy aniline amide treatment prevented decrease in RNA for trkC, enhanced expression of trkB RNA and p75NGFR. Retinoic acid ortho-hydroxy aniline amide treatment for 5 days increased the baseline expression of c-fos mRNA following stimulation with NGF, BDNF, and NT-3. Treatment of cultures with retinoic acid ortho-hydroxy aniline amide for 5 days followed by 5 days in serum alone increased Map2ab-positive cells compared to that of control. Therefore, retinoic acid ortho-hydroxy aniline amide is an effective agent for inducing neuronal differentiation and proliferation and is even more potent than the parent retinoic acid.